Biomarkers for Early Detection of Renal Injury in Fetuses With Congenital Urinary Tract Obstruction - Kostic, Dusan; Kato, André Henrique Teruaki; Lima, Laila; Palmeira, Patricia; Francisco, Rossana Pulcineli Vieira; Bunduki, Victor; Koch, Vera Hermina Kalika (Frontiers in Urology, 2022)
Objective. To investigate a selection of renal injury biomarkers in fetal congenital lower urinary tract obstruction (LUTO) and their potential to identify renal damage in significant obstructive patterns, eventual benefit of fetal intervention and to predict the outcome in terms of survival. Study design. Ten fetuses with congenital LUTO were submitted to fetal urine analysis that included six renal injury biomarkers: Neutrophil gelatinase-associated lipocalin (NGAL), Kidney injury molecule-1 (KIM-1), Transforming growth factor beta-1 (TGF-β1), Retinol-binding protein (RBP), Cystatin C (uCyC) and microalbuminuria (µALB). The results were compared with urinary parameters of patients born with LUTO and healthy newborns. Result. The majority of fetal biomarker levels showed significantly higher values when compared to all groups at birth with exception of KIM-1 and μALB. RBP and uCyC, performed with 100% accuracy to identify severe renal damage in fetal LUTO. Conclusion. Urine CyC, NGAL, RBP, and TGF-ß1, demonstrated high capability to identify significant renal impairment due to severe LUTO and may contribute to currently used fetal medicine diagnostic parameters.